Empire state a love story (or not) - Shiga, Jason. (Laura Ann); Pham, John. 1906-1998. 1933- 1960- 1955- (Susan Maxine); 1952- 1949- 1954-; 1923- (Melvin Lawrence) (New York Abrams ComicArts, 2011)
When his best friend, Sara, moves to New York City, Jimmy--who loves science fiction but knows very little about the outside world--works up the courage to travel cross-country by bus to see her, and perhaps change their relationship.
Keywords: Man-woman relationships -- Comic books, strips, etc; Graphic novels